Analisis Penggunaan Notebooklm dalam Mendukung Pemahaman Konsep SPLTV Siswa Kelas X SMAIT Kyai Sekar Al-Amri - Afrilina Raudhotul Jannah; Nuryami (IEC: Journal of Educational Innovation, 2026)
The Three-Variable Linear Equation System (SPLTV) is an essential topic in the Grade X senior high school mathematics curriculum that requires deep conceptual understanding; however, preliminary observations revealed that 60% of students scored below the Minimum Completeness Criteria (KKM), attributed to conventional teacher-centered instruction that had not optimally facilitated conceptual understanding. This study aims to analyze the use of NotebookLM in supporting students' conceptual understanding of SPLTV in Grade X. The research employed a descriptive qualitative approach with instruments consisting of test questions, questionnaires, and interview guidelines, analyzed using the interactive model of Miles, Huberman, and Saldaña. The research subjects were 30 female students of Grade X at SMAIT Kyai Sekar Al-Amri, Probolinggo. The results showed that all students obtained test scores ranging from 80–100 with an average of 91.33, along with positive responses from the questionnaires and interviews regarding the ease of use and benefits of NotebookLM, although some students still experienced difficulties in determining the appropriate solving method and therefore still required teacher guidance.